Perlindungan Perempuan dalam Hukum Perkawinan di Indonesia - Maula, Bani Syarif (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
The Indonesian Constitutional Court granted part of the claim for the judicial review lawsuit on Law No. 1 of 1974 concerning Marriage for Article 7 Paragraph 1 related to the age of marriage. The article is considered discriminatory against women and is considered legalizing child marriages because the lowest age limit for women can be married is 16 years old, different from the lowest age limit for men, 19 years old. The global consensus on the need to abolish early marriage, forced marriage, and child marriage is actually made and agreed upon by UN member countries, including Indonesia. There are a number of adverse effects that can arise in child marriage, such as impacts related to health, education and economic aspects, including violations of children's rights. This paper examines the age limit of marriage in the perspective of Islamic law, which can then become state policy. Marriage is a legal act that requires the doers to meet the criteria of legal competency. Marriage also requires the responsibility of the parties to fulfill their rights and obligations, so that the aspect of maturity in marriage is a must.